Can you guys help me solve this equation with step-by-step help, please...
1 answer:
Step-by-step explanation:
-2x - 5y = 16___(1)
2x - 3y = -16___(2)
(1) + (2) ==> -2x -5y = 16
(+) <u>2x -3y = -16</u>
-8y = 0
y = 0/-8
y = 0
y=0 in (1)
(1)---> -2x-5y =16
-2x - 5(0) = 16
-2x - 0 = 16
-2x = 16
x = 16/-2
x = -8
x = -8 , y = 0
-5x + 2y = 11__(1) ; -3x + 4y = -13___(2)
multiply eqn(1) with 2
2 × (1) : -10x + 4y = 22___(3)
(3) - (2) :. -10x + 4y = 22
(-) <u>-3x </u><u>+</u><u> </u><u>4</u><u>y</u><u> </u><u>=</u><u> </u><u>-</u><u>1</u><u>3</u>
-7x = 35
x = 35/-7
x = -5
x=-5 in (1)
(1) : -5x + 2y = 11
-5(-5) + 2y = 11
25 + 2y = 11
2y = 11 - 25
2y = -14
y = -14/2
y = -7
x = -5 , y = -7
You might be interested in
Answer:
<h2>2/5 </h2>
Step-by-step explanation:
<h2>Hope it help & study well</h2>
Answer:
The first one
Step-by-step explanation:
We simplify this inequality to x>4. This means it is moving past the four to the right with an open dot
4,000 if you set it up as unit rate with .15 on btm
the answer is the bottom one on the first row
Answer:
dude how are you supposed to figure this out????
Jiri age is 23
Step-by-step explanation: